The Development of Student Worksheets Based on Simulation Methods - Mispandi Mispandi; Endang Mulyani (Faculty of Economics, State University of Jakarta., 2020)
This study aims to determine, the process of development, eligibility and student responses to student worksheets based on simulation methods. This type of research is Research and Development (R&D), using the Borg & Gall development model. The subjects of the study were students of class XI of SMA Negeri 1 Sambelia. The results showed that the results obtained were validated material, language, and design 3.44 with the appropriate category, and the students' response was 4.16 with the appropriate category. The results showed that the development of student worksheets based on simulation methods was feasible to use and influenced student learning outcomes in economic subjects. The contribution of research as a tool in the learning process for teachers and students in schools.